KEARIFAN LOKAL LUBUK LARANGAN SEBAGAI UPAYA PELASTARIAN SUMBERDAYA PERAIRAN DI NAGARI SIKUCUR KECAMATAN V KOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN PROVINSI SUMATERA BARAT - Annisa Prima Dani; Firman Nugroho; Victor Amrifo (Fakultas Perikanan dan Kelautan, Universitas Riau, 2016)
The research was conducted on February 2016 in Nagari Sikucur , V Koto Kampung Dalam Sub District, Padang Pariaman District, West Sumatra Province.The purpose of this research was to 1) Describe the form of local wisdom as a effort of aquatic resource conservation in Nagari Sikucur , V Koto Kampung Dalam Sub District, Padang Pariaman District, West Sumatra Province 2) Find out the effort of county to institutionalize lubuk larangan as local wisdom 3) Identify the strategy and policy of sustainability local wisdom. Lubuk larangan is a part of the river or the lake which is rather deep, sheltered and preferred by various fishes as a place to breed, allowing them to grow and reproduce naturally, and is banned for hunting in a given time period. The method used in the research was the quantitative research method. The result showed that the local wisdom in Nagari Sikucur is formed as lubuk larangan, the management of lubuk larangan is in form of surveillance, regulation, and sanction. The strategy undertaken is by keep doing the mutual cooperation once in a week